The Consciousness of Black Identity in Amiri Baraka’ Poems (Universitas Islam Negeri Sunan Ampel Surabaya, 2013)
This study explores the significance of new identity for the African-American people as a protest against the discriminative pressures happened from 1960s to 1970s through Amiri Baraka‟s poems. Baraka said that by proposing their own identity as African-blood Americans, they can show their existence in the American society. He proposed an awareness on the existence of Afican-American society in all aspects of life, such as the different characters and appearances in literature and tradition. Baraka tries not to follow the traditional rules anymore. With his poems, Amiri Baraka engaged the African-Americans to produce literary products with a strong and prominent style of writing, and adopt African languages. Baraka also supports the movements of so-called Black Culture which supported by African-American activists through their poems on the awareness of their real identity as Black People.